Improving the Hsp90 Inhibitors Containing 4-(2,4-Dihydroxyphenyl)-1,2,3-thiadiazole Scaffold: Synthesis, Affinity and Effect on Cancer Cells - Kazlauskas, Egidijus; Brukstus, Algirdas; Petrikas, Herkus; Petrikaite, Vilma; Cikotiene, Inga; Matulis, Daumantas (Anti-Cancer Agents in Medicinal Chemistry, 2017)
Background: Human Hsp90 chaperone inhibitors are known to be potential anticancer drugs. Previously we have shown a couple of 5-aryl-4-(2,4-dihydroxyphenyl)-1,2,3-thiadiazoles to be promising anticancer agents. Objective: To improve the compounds containing 4-(2,4-dihydroxyphenyl)-1,2,3-thiadiazole scaffold as human Hsp90 inhibitors. Method: We employed chemical synthesis to obtain new compounds and assayed their binding to Hsp90 using the fluorescence thermal shift assay and used MTT assays to determine their effect on cancer cells. Results: A series of compounds containing the 4-(2,4-dihydroxyphenyl)-1,2,3-thiadiazole scaffold were synthesized as Hsp90 inhibitors. Analysis of their binding to the recombinant N-terminal domain of Hsp90 revealed that four of these compounds bound to Hsp90 with Kd of 0.6 to 0.8 nM. The compounds fully inhibited the growth of all tested cancer cell lines: A549 (lung adenocarcinoma), IGR39 (melanoma), and U87 (glioblastoma), with the effective antiproliferative concentration (EC50) of the compounds reaching 0.35 μM. Conclusion: This series of 14 novel and efficient Hsp90 inhibitors provided additional information on the structure-activity relationship of Hsp90 inhibitors and may be further developed into drugs targeting Hsp90.
Keywords: fluorescence thermal shift assay